PERANAN PENGACARA DALAM PROSES PERSIDANGAN PADA KASUS ANAK SEBAGAI PELAKU TINDAK PIDANA DI PENGADILAN - Raden Gatot Kurniawan; Yanto Yanto; Tasmilan Tasmilan (Universitas Janabadra, 2018)
The study aims to examine and analyze the role of attorney on judicial process in the case of child criminals in Bantul Appellate Court. The obstacles faced by the lawyers in convincing the judges deal with the fact that children should be protected from punishment that leads to injustice and the way to overcome the obstacles is that the judges are supposed to make a fair decision on the issue. It is Juridical Empirical research. The specification employed in this research is analytical description. This research uses primary and secondary data. The data collection is completed by conducting document analysis and interview through qualitative research. Based on the result of the research, it is concluded that the process of court against child criminals according to Laws No. 11 year 2012 about juvenile court system in Bantul Appellate Court starts from the court’s receiving and analyzing the case. The prosecutor then attends the prosecution in accordance with his conviction, then the lawyer provides convincing defense before the judge that the children considered the future generations should be protected to the maximum extent and make the imprisonment be the last alternative for the them, and the lawyer attempts to convince the judge to make decision on returning the children to their parents guardians.Keywords: Lawyer, Child Criminals Justice System, Bantul Appellate Court